BARRIERS TO USING INTERNET IN TEACHING BY COLLEGE OF AGRICULTURE FACULTY-UNIVERSITY OF MOSUL - Mohammed Jamil (Mesopotamia Journal of Agriculture)
The purpose of this study was to provide baseline data concerning barriers to online teaching by the faculty of the college of agriculture-University of Mosul. 207 of the faculty in the college of agriculture were included in the survey, and 188 responded to instrument consisted measurements of faculty perceptions of  their level of competence to access related issues to teaching from internet, value of internet to teaching and learning, and level of administrative support to using online in teaching and learning. Findings indicated that faculty members had moderate ability to use internet in their teaching. The agricultural faculty members valued internet and recognized that it will be an important part of the instructional process. Infrastructure was perceived as multifaceted and in general lacking in this institution.